2022
DOI: 10.3390/ijms23031131
|View full text |Cite
|
Sign up to set email alerts
|

Rab21 Protein Is Degraded by Both the Ubiquitin-Proteasome Pathway and the Autophagy-Lysosome Pathway

Abstract: Rab21 is a GTPase protein that is functional in intracellular trafficking and involved in the pathologies of many diseases, such as Alzheimer’s disease (AD), glioma, cancer, etc. Our previous work has reported its interaction with the catalytic subunit of gamma-secretase, PS1, and it regulates the activity of PS1 via transferring it from the early endosome to the late endosome/lysosome. However, it is still unknown how Rab21 protein itself is regulated. This work revealed that Rab21 protein, either endogenousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Rab21, a member of the Ras superfamily of small GTPases, can bind to the 𝛼 subunit of integrin, promote its endocytosis to early endosomes, and alter the localization of integrins in cells. [16][17][18][19] To recognize how DATS increases the endocytosis of integrin 𝛽1 in colonic epithelial cells, effect of DATS on the expression of Rab21 was examined. The results showed that DATS had no evident impact on the mRNA and protein expression of Rab21 in NCM 460 cells (Figure 7D).…”
Section: Dats Promotes Fak Phosphorylation Migration and Wound Healin...mentioning
confidence: 99%
“…Rab21, a member of the Ras superfamily of small GTPases, can bind to the 𝛼 subunit of integrin, promote its endocytosis to early endosomes, and alter the localization of integrins in cells. [16][17][18][19] To recognize how DATS increases the endocytosis of integrin 𝛽1 in colonic epithelial cells, effect of DATS on the expression of Rab21 was examined. The results showed that DATS had no evident impact on the mRNA and protein expression of Rab21 in NCM 460 cells (Figure 7D).…”
Section: Dats Promotes Fak Phosphorylation Migration and Wound Healin...mentioning
confidence: 99%
“…Interestingly, our GSE2599 dataset prediction and preliminary experiments revealed a low expression of UBR1 in SCI rats. Meanwhile, ubiquitination and autophagy, two predominant intracellular degradation pathways, are distinct in their mechanisms but inextricably connected in controlling protein quality and maintaining cellular homeostasis ( P. Liu et al, 2022 ). A recently published article demonstrated that UBR1 facilitates the clearance of misfolded MLC1 during Ca 2+ stress by eliciting p62-mediated selective autophagy ( B.B.…”
Section: Introductionmentioning
confidence: 99%